Evaluation of dried distiller’s grains and roughage source in steam-flaked corn-based finishing diets - S. Uwituze; G.L. Parsons; M.K. Shelor; K.K. Karges; M.L. Gibson; Brandon E. Depenbusch; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2008)
Dried distiller's grains with solubles (DDGS) are the main byproduct of dry milling, the process used most frequently for fuel ethanol production. DDGS consist of the spent grains following ethanol distillation and are high in protein, fat, fiber, and minerals. Alfalfa hay and corn silage are roughages most commonly included in feedlot diets and are one of the most expensive ingredients in feedlot diets on an energy basis. Comparing use of alfalfa hay and corn silage in conjunction with DDGS can provide useful information on how to obtain maximum benefit from these ingredients. Our objective was to evaluate the use of corn DDGS as a partial replacement for steam-flaked corn when corn silage or alfalfa hay were used in feedlot diets.
Keywords: Cattlemen' s Day; 2008; Kansas Agricultural Experiment Station contribution; no. 08-212-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 995; Beef; Cattle; Dried distiller’s grains with solubles (DDGS); Corn silage; Alfalfa